Effects of environmental stress on forest crown condition in Europe. Part II: Estimation of stress induced by meteorology and air pollutants (Water, Air, & Soil Pollution, 2000)
In order to assess the relationship between environmental stress and crown condition of forest trees monitored since 1986 in Europe, estimates of stress factors, including temperature stress, drought stress and air pollution stress, were derived with the best data, methods and models currently available. This paper presents information on the methods used to derive such stress factors, and on the overall ranges, the temporal trends, the spatial distribution and the reliability of the calculated stress factors. The temperature stress indices did not show much temporal variation between 1985 to 1995. As expected spatial patterns were north-south orientated, going from colder northern regions to warmer southern regions. The calculated relative transpiration showed a more complex pattern, coinciding to a large extend with patterns of rainfall and temperature. Potential acid deposition decreased between 1986 and 1992, but remained fairly constant after 1992. The strong decrease was mainly the result of the decrease in SOx deposition, and to a small decrease in NOy deposition. Highest levels of the S and N deposition were calculated in Central and Western Europe. Base cation deposition was largest in coastal areas and in southern Europe. This is mainly due to soil dust, Sahara dust and sea salt. Base cation deposition can compensate almost entirely for the potential inputs in the south of Europe, whereas in central Europe it equalled about 25% of the potential acid input. A comparison between site speciﬁc modelled deposition and deposition derived from throughfall data showed that the total acid deposition is usually overestimated by the model, whereas the total nitrogen deposition is underestimated, especially at plots with high nitrogen loads. There is, however, a signiﬁcant correlation between measured and modelled data for all S and N deposition, thus allowing their use in a statistical analyses.